Possibilities of drug therapy for uterine leiomyoma in reproductive age - Mekan R. Orazov; Viktor E. Radzinsky; Lemin M. Leffad (IP Berlin A.V., 2021)
Uterine leiomyoma, along with endometriosis, occupies a leading position in the structure of gynecological diseases associated with hyperproliferation. The disease can negatively affect the reproductive potential, gynecological health, somatic status and quality of life of women. The only radical "cure" for the disease is hysterectomy. Therefore, clinical research and assessment of the effectiveness of drug therapy for uterine leiomyoma is one of the most important tasks of modern gynecology, primarily for the health improvement of young women striving to preserve reproductive function. From the point of view of world demography (declining birth rates in the world and depopulation in European countries), the search for new pharmacological agents for the treatment of fibroids is not only a medical problem, but also a global socio-economic problem